Plant species richness does not attenuate responses of soil microbial and nematode communities to a flood event. (October 2015) - Wagner, Daniela; Eisenhauer, Nico; Cesarz, Simone
Abstract: Human activities are causing climatic changes and alter the composition and biodiversity of ecosystems. Climate change has been and will be increasing the frequency and severity of extreme climate events and natural disasters like floods in many ecosystems. Therefore, it is important to investigate the effects of disturbances on ecosystems and identify potential stabilizing features of ecological communities. In this study, soil microbial and nematode communities were investigated in a grassland biodiversity experiment after a natural flood to investigate if plant diversity is able to attenuate or reinforce the magnitude of effects of the disturbance on soil food webs. In addition to community analyses of soil microorganisms and nematodes, the stability indices proportional resilience, proportional recovery, and proportional resistance were calculated. Generally, soil microbial biomass decreased significantly due to the flood with the strongest reduction in gram-negative bacteria, while gram-positive bacteria were less affected by flooding. Fungal biomass increased significantly three months after the flood compared to few days before the flood, reflecting elevated availability of dead plant biomass in response to the flood. Similar to the soil microbial community, nematode community structure changed considerably due to the flood by favoring colonizers (in the broadest sense r-strategists; c–p 1, 2 nematodes), particularly so at high plant diversity. None of the soil microbial community stability indices and few of the nematode stability indices were significantly affected by plant diversity, indicating limited potential of plant diversity to buffer soil food webs against flooding disturbance. However, plant diversity destabilized colonizer populations, while persister populations (in the broadest sense K-strategists; c–p 4 nematodes) were stabilized, suggesting that plant diversity can stabilize and destabilize populations depending on the ecology of the focal taxa. The present study shows that changes in plant diversity and subsequent alterations in resource availability may significantly modify the compositional shifts of soil food webs in response to disturbances. Graphical abstract: Highlights: We studied interactive effects of plant diversity and a natural flood on soil biota. The structure of soil microbial and nematode communities changed due to the flood. Few of the stability indices were significantly affected by plant diversity (PD). PD stabilized or destabilized populations depending on their ecology. PD may modify shifts of soil food webs in response to disturbances.